The first modern attempts to delimit the Pyrenean border: the Caro-Ornano Franco-Spanish commission and its cartographic legacy (1784-1792) - García Álvarez, Jacobo; Puyo, Jean-Yves (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
This article examines the first attempts to establish a modern delimitation of the Pyrenean border between Spain and France during the 18th century. Particular attention is paid to the cartographic work of the Caro-Ornano Boundary Commission (1784-1792), whose military engineers were in structed to plot a detailed map of the entire Spanish-French border. Although unfinished, the map was designed using modern trigonometric methods and thus represents an outstanding contribution to the history of cartography, both for its scientific quality and detail and for the international collaboration that it entailed.